Observations on the action of type A botulinum toxin on frog neuromuscular junctions - Boroff, D. A. (1974)
1. Progressive block of neuromuscular transmission in frog sartorius and gastrocnemius preparations by haemagglutinin-free crystalline Type A botulinum toxin (BTX) was investigated by in vitro application and by injection of the toxin into living animals. 2. Neuromuscular block was characterized by (a) decline in amplitude of evoked twitch contractions, (b) decline in amplitudes of end-plate potentials (e.p.p.s) and (c) changes in statistical characteristics of spontaneous miniature end-plate potentials (m.e.p.p.s). 3. Progress of the block was enhanced by nerve stimulation. 4. A decrease in frequency to less than 0·1/sec and decreased average amplitudes of m.e.p.p.s preceded observable impairment of neuromuscular transmission. These changes occurred as early as 3 hr after injection of the toxin into dorsal lymph sacs. 5. The amplitude distributions of m.e.p.p.s changed from a normal distribution to one that showed an increased skewness toward smaller amplitudes as the block progressed. These changes were first detectable as early as 75 min following addition of the toxin to the bath. 6. At later stages of toxin action, e.p.p.s began to decrease in amplitude and eventually failed altogether. E.p.p.s showed a normal quantal variation at very early stages in the block in Mg(2+)-treated preparations. At later stages of the block, it was not possible to test the quantal make-up of the e.p.p. 7. At all stages before complete failure it was possible to obtain normal or greater than normal degrees of synaptic facilitation with paired stimuli to the nerve. This aspect of the coupling of nerve terminal depolarization to transmitter release appears to be relatively unaffected by BTX. 8. Electrical depolarization of nerve terminals in partially blocked preparations evoked a maintained discharge of m.e.p.p.s with an amplitude distribution similar to that of the spontaneous m.e.p.p.s; hyperpolarization of the terminals evokes a distinctly larger class of m.e.p.p.s. In fully blocked preparations, depolarization of the terminals does not evoke transmitter release whereas hyperpolarization continues to yield the larger class of m.e.p.p.s. 9. It is proposed that the neuromuscular block caused by BTX is due to impairment of a process by which vesicles become charged with transmitter before release.